2020
DOI: 10.1186/s40337-020-00301-8
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentoring for individuals with an eating disorder: a qualitative evaluation of a pilot program

Abstract: Background: After receiving intensive medical treatment; individuals with eating disorders often require ongoing care to maintain their recovery, build social networks, and reduce risk of relapse. Methods: To address this important transition period, a six-month peer mentoring program was developed and piloted in Melbourne, Australia. Twelve adults with a past history of an eating disorder (mentors) were paired with 14 individuals with a current eating disorder (mentees). Pairs met for thirteen mentoring sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…One idea raised in the current study was, rather than focusing on service-provided interventions for carers, peer-based support for carers could be particularly bene cial for this population. Previous studies exploring peer support and peer mentoring in carer and ED elds have found that this approach lessens feelings of isolation and exclusion due to the sense of shared experience, and can create feelings of hope [34,35]. With carers in the present study describing experiences of social isolation, hopelessness, and frustration with existing services due to a perceived lack of understanding of co-occurring ASC and ED, it is possible that peer-based support could be appropriate for this population.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…One idea raised in the current study was, rather than focusing on service-provided interventions for carers, peer-based support for carers could be particularly bene cial for this population. Previous studies exploring peer support and peer mentoring in carer and ED elds have found that this approach lessens feelings of isolation and exclusion due to the sense of shared experience, and can create feelings of hope [34,35]. With carers in the present study describing experiences of social isolation, hopelessness, and frustration with existing services due to a perceived lack of understanding of co-occurring ASC and ED, it is possible that peer-based support could be appropriate for this population.…”
Section: Discussionmentioning
confidence: 76%
“…With carers in the present study describing experiences of social isolation, hopelessness, and frustration with existing services due to a perceived lack of understanding of co-occurring ASC and ED, it is possible that peer-based support could be appropriate for this population. However, drawbacks described in previous studies include the di culty of ending relationships at the end of the mentorship programme, and managing boundaries [35]. In addition, peer support alone may not be su cient in helping carers, and additional or alternative sources of help may be required [34].…”
Section: Discussionmentioning
confidence: 98%
“…One idea raised in the current study was, rather than focusing on clinical service-provided interventions for carers, peer-based support for carers could be particularly beneficial for this population. Previous studies exploring peer support and peer mentoring in carer and ED fields have found that this approach lessens feelings of isolation and exclusion due to the sense of shared experience, and can create feelings of hope [ 40 , 41 ]. With carers in the present study describing experiences of social isolation, hopelessness, and frustration with existing services due to a perceived lack of understanding of co-occurring ASC and ED, it is possible that peer-based support could be appropriate for this population.…”
Section: Discussionmentioning
confidence: 99%
“…With carers in the present study describing experiences of social isolation, hopelessness, and frustration with existing services due to a perceived lack of understanding of co-occurring ASC and ED, it is possible that peer-based support could be appropriate for this population. However, drawbacks described in previous studies include the difficulty of ending relationships at the end of the mentorship programme, and managing boundaries [ 41 ]. In addition, peer support alone may not be sufficient in helping carers, and additional or alternative sources of help may be required [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review is limited in terms of the population group considered, namely, those with physical health conditions. Alternative populations that have been shown in the literature to utilize peer support include families and carers of individuals with physical health conditions [29][30][31]; mental health populations [32][33][34][35][36]; children and young people [37][38][39][40]; 'at-risk' groups [41]; veterans [42] and those that are homeless [43].…”
Section: Limitationsmentioning
confidence: 99%